Meningkatkan Hasil Belajar Menulis Narasi dengan Strategi Quantum Writing Bebantuan Media Picture and Picture bagi Siswa Kelas V SD - Nurjani, Nurjani; Fauziah, Muhardila (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
Initial observations were the initial foundation for carrying out this research. It was found that many of the fifth grade students at SDI al-Azhar Muhammadiyah still had difficulty writing narratives with evidence that their overall average completion rate had not yet reached the predetermined KKM namely 70. The research used namely PTK using two cycles, each cycles has for steps, namely planning, action, observation, and reflection. The subjects of this research were class V students at SDI al-Azhar Muhammadiyah consisting of 38 student. Then this research uses research isntruments in the from of observations and tests. The results of this research show that there is an increase in students learning from cycles I to cycles II yhe average overall students completion was 68,94. Then in cycles II there was a significant increase, namely with an overall average og 78,68. So it can be concluded that the application of the quantum writing strategy assisted by picture and picture media can solve problems in the classroom, namely it can provide solutions to the learning to write narratives for class V students at SDI al-Azhar Muhammadiyah.